Handbook of Florida Agricultural Laws: Index - Michael T. Olexa; Ian Alperstein; Joseph Fischer (EDIS)
Revised! Circular 1224, a handbook broken into 8 parts, by Michael T. Olexa, Ian Alperstein, and Joseph Fischer, provides an accurate, current, and authoritative summary of the principal Florida laws that directly or indirectly relate to agriculture. It provides a basic overview of the many rights and responsibilities that farmers and farmland owners have under Florida laws. Published by the UF Department of Food and Resource Economics, December 2007.